ANALYSIS OF SINGLE CHANNEL-MULTI PHASE QUEUE MODEL - PURWANDA, SYAFIQ ANNAS (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
This research is a type of research based on case studies, where is the research withUSING a descriptive approach to explain variables what will be studied. The purpose of thisprogram was to find out the Queuing System Model of the Office of Central Java Province inPemalang District, to find the size pattern of service at UP3AD Central Java Province, andto test the arrival pattern Poisson distribution and whether Service Time is distributedExponential. This research is conducted by observing the rate of arrival of taxpayers perminute and also the time of service for taxpayers per minute. This study was tested usingthe Kolmogorov-Smirnov Conformity Test which was assisted by SPSS and Microsoft Excelapplications.